Experiences and Perceptions of Elite Female Athletes on the Menstrual Cycle’s Impact on Performance and Achievements in Sports Competitions in East Java - Hanifah, Khilmi; Widiawati, Prisca; Ramadhan, Muhammad Putra (Indonesian Journal of Sport Management, 2025)
Background: Menstruation can be an obstacle for athletes in sports activities, as female athletes continue to participate in training and competitions despite menstruating. This perception can lead to discrimination and a lack of understanding of the conditions faced by female athletes. Purpose of the Study: This study aims to understand how the menstrual cycle affects the physical performance and achievements of elite female athletes. Method: This research employs a non-experimental quantitative approach. The type of research is descriptive quantitative, using a survey approach. The population of this study comprises female athletes who have experienced the menstrual cycle from various sports disciplines in East Java Province, with sample totaling 103 elite female athletes. The instrument used in this research is a questionnaire addressed to the sample of female athletes. Results: The findings reveal that most elite female athletes in East Java, particularly in combat sports, experience irregular menstrual cycles and menstrual pain. However, these factors do not significantly impact their training and performance, with most athletes neither using hormonal contraception nor experiencing major issues while training during menstruation. Conclusion: Most elite female athletes in East Java experience irregular menstrual cycles and pain on the first day. However, training during menstruation generally does not have a significant impact on their performance. Implications: Training program management should consider the menstrual cycle to help elite female athletes maintain optimal performance and manage pain when competing.